Characterization of students with high intellectual capacity: the approach in the Portuguese school context and importance of teacher training for their educational inclusion - García-Perales, Ramón; Rocha, Alberto; Aguiar, Ana; Almeida, Ana Isabel S. (Frontiers in Psychology, 2024)
This paper takes a terminological approach to the concept of high intellectual abilities, highlighting the distinctive aspects of the way it is addressed in the Portuguese educational context. It outlines the existing conceptual differentiation in the field of higher abilities, emphasizing how the main characteristics are described and including the strengths and weaknesses of current teaching and learning processes in Portugal. As we will show, educational work with these students in Portuguese schools is characterized by unequal regulation compared to other educational needs, by an imbalance of educational processes aimed at these gifted students, and by clear underdiagnosis that sometimes leads to them being ignored in the classroom, with the consequent harm that this can cause to their overall development and to their academic and professional careers. The paper emphasizes the importance of teacher training in Portugal as an aspect that could be key to reversing, as far as possible, this gap in educational processes—which currently include educational inclusion for all their students as part of the key action principles in the Portuguese educational system.